Peningkatan Kapasitas Produksi Dan Kualitas Keripik Talas Situjuh Melalui Branding Kemasan Dan Diversifikasi Rasa - Rahayuningsih, Tri; Armalita, Rani; Febtriko, Anip (Lembaga Dongan Dosen, 2025)
Taro chips are one of the typical snack products that are widely developed by Micro, Small, and Medium Enterprises (MSMEs) in West Sumatra Province. However, limitations in production and packaging technology are the main obstacles in improving the quality and competitiveness of products in the market. This community service activity was carried out to increase the production capacity and quality of taro chips through the application of technological innovations in the form of automatic slicing machines and the development of marketing strategies based on brand strengthening and attractive packaging designs. The implementation method includes technical training on the use of slicing machines, assistance in flavor diversification (balado and seaweed), and education on digital packaging and marketing. The results of the activity showed an increase in production efficiency, consistency of the shape and thickness of the sliced chips, and a positive market response to new flavor variants and more attractive packaging. In conclusion, the touch of technology and marketing innovation has proven to be able to increase the competitiveness of MSME products, while contributing to increasing the income of target partners.